The Effect of E-learning Based Schoology on the Learning Outcomes in Nursing Program - Dzul Rachman; Sunarti; Arbain (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2019)
The fast advance of information technology has attempted English teachers with innovative and recent teaching models. This study focuses on the use of Schoology in ESP nursing class. The quantitative research was done with one group pre-test and post-test design. The samples were the second semester ESP class of Nursing program as an experimental group that consists of 122 students and 122 students as a control group. The instruments used the test to measure the students’ cognitive achievement. The inferential analysis used in this research was a t-test. Based on the results of Group Statistics, it is found that the average value of the posttest for the control group was 61.05 while the experimental group was 84. Thus, statistically, it can be concluded that there are significant differences in learning outcomes between the control group with the lecture method and the experimental group using Schoology. In other words, the use of Schoology is effective in learning also helps improve English learning outcomes of students of Nursing Program.